FORMULATION AND EVALUATION OF FAST DISSOLVING TABLET OF VALSARTAN BY USING MIXED HYDROTROPY TECHNIQUE - Prashant L. Pingale, Nandini S. Chavan, Pragya Sharma, Shagun Swaroop, Kuldeep Ramteke, Gaffar Sayyed, Shivraj Shivpuje, Ujjwala V. Ghule, Megha Mishra, Vinod Thakare (South Eastern European Journal of Public Health, 2025)
The purpose of this labor is to create and assess quick-dissolving pills of Valsartan utilizing the mixed hydrotropy concept to enhance its solubility and dissolution rate. Valsartan, an antihypertensive agent, exhibits poor aqueous solubility, posing challenges in achieving prompt therapeutic action. The mixed hydrotropy approach leverages a combination of hydrotropic agents to improve solubility and bioavailability. In this study, Nicotinamide, Sodium benzoate, Ammonium acetate, Sodium acetate and Lactose were selected as hydrotropic agents and incorporated into the tablet's makeup. After the tablets were prepared using the simple compression method, we evaluated the formulations based on pre-compression properties like bulk density, tapped density, and compressibility index. Evaluations were conducted on post-compression parameters, including hardness, friability, weight variation, wetting time, water absorption ratio, in vitro dispersion time, and drug concentration, to ensure tablet quality and uniformity. The efficacy of the mixed hydrotropy strategy has been demonstrated by in vitro dissolving studies, which demonstrated a significant increase in the rate of valsartan dissolve from the FDTs in comparison to pure medicine and conventional tablets. Differential Scanning Calorimetry (DSC) analyses indicated no significant drug-excipient interactions, ensuring the stability of the formulation. In conclusion, the mixed hydrotropy approach proved to be a viable and efficient method to increase the rate of solubility and dissolved Valsartan, leading to successful development of fast dissolving tablets that could potentially improve patient compliance and therapeutic efficacy in hypertension management.